Kształtowanie struktury kapitałowej Kompanii Piwowarskiej i jej wpływ na rentowność w latach 1994-2005 - Polaczek, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The study presented in this paper shows that assets, particularly their size, quality and structure together with the transformation in a longer period of time, influence significantly financial results. Generated financial results have impact in turn on the return on capital and the costs of gaining and maintaining of capital. In the Brewery Company, the main source of high return on their own capital was the high profitability of involved assets and relatively big share of foreign capital in financing the assets. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 387-396